2021
DOI: 10.1002/adma.202007434
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Method for High‐Speed Fluorination of Metal Oxides by Spark Plasma Sintering Yields Ta3O7F and TaO2F with High Photocatalytic Activity for Oxygen Evolution from Water

Abstract: The search for clean, low-cost, and renewable energy sources is one important challenge of modern industrial societies. [1] Hydrogen generated by photochemistry has been identified as a promising energy carrier with high energy density and zero CO 2 emission while being environmentally clean. [2,3] To set up a light-driven and hydrogen based economy an exploration of new materials for eco-friendly, economically viable, stable, and efficient photocatalysts is needed. [4] Noble metals like platinum, iridium, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 67 publications
0
54
0
Order By: Relevance
“…The lower photoelectrocatalytic HER enhancement by TaO 2 F than TiOF 2 can be related to their optical band gap. A recent study reported that TaO 2 F presents an energy band value of ≈4.10 eV, so it is expected to be less photoactive than TiOF 2 when both are exposed to the light source (660 nm) in this work. Overall, Cr 2 AlC and F-Cr 2 AlC presented the lowest overpotential in their respective category.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The lower photoelectrocatalytic HER enhancement by TaO 2 F than TiOF 2 can be related to their optical band gap. A recent study reported that TaO 2 F presents an energy band value of ≈4.10 eV, so it is expected to be less photoactive than TiOF 2 when both are exposed to the light source (660 nm) in this work. Overall, Cr 2 AlC and F-Cr 2 AlC presented the lowest overpotential in their respective category.…”
Section: Resultsmentioning
confidence: 95%
“…As a confirmation, the cubic-like structures observed on the surface of F-MAX in Figure 1a,c,d can be attributed to TaO 2 F and TiOF 2 since both possess a simple cubic crystal structure and the cubic morphology agrees with the reported works. 44,45 Despite fluorine being detected in F-Cr 2 AlC, the etching effect on the Al layer is least prominent, with the smallest separation between layers, the lowest amount of F within the sample, and no Cr-based oxyfluoride structures were detected. The different fluorination effects can be related to the properties of individual MAX and its corresponding metal oxides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These include metal oxides such as TiO 2 , hematite, ZnO, BiVO 4 , rare earth metals, coordinate complexes, (oxy)sulfides, (oxy)fluorides, and (oxy)nitrides with d 0 and d 10 electronic configuration. [10][11][12][13] Nevertheless, most of these suffer from intrinsic limitations of large bandgap (> 3.0 eV), poor solar light-harvesting ability and photostability, and low conversion efficiency. [14] Most recently, organic conjugated polymers have established their potential to be a versatile platform for water splitting owing to their low cost, superior photo-/thermostability, and tunable structure and properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, water splitting with the lowest carbon footprint as the most promising method to generate hydrogen has been extensively researched with a rich reserve of electrocatalysts for hydrogen evolution (HER). With the practical use of high cost noble metal Pt as the state of the art catalyst, a pool of non-noble metal catalysts have been explored, yet it still leaves behind unfilled gaps. A clear understanding of the HER mechanism described in acidic/basic medium will provide education about the challenges and possibilities (Figure ). Briefly, H 2 evolution takes place at the cathode of a water electrolyzer and follows two elementary steps. , …”
Section: Introductionmentioning
confidence: 99%